Exploring The Role Of Qris Digital Payments In The Operational And Financial Performance Of Muslim Msmes In Pamekasan: A Phenomenological Study - Khotibul Umam; Umarul Faruq; Nadya Apriza Azizi Faruq; Naili Zulfa Hidayati Hidayati (Academic Bright Collaboration, 2026)
Purpose – This study explores the role of QRIS digital payments in shaping the operational and financial performance of Muslim MSMEs in Pamekasan, focusing on their lived experiences within a socio-religious context. Methods – A qualitative phenomenological approach was employed to understand how Muslim MSME traders experience and interpret QRIS in their daily business activities. Data were collected through in-depth interviews, observations, and document analysis involving 20 Muslim MSMEs from diverse business sectors. The analysis followed phenomenological procedures to identify key themes and capture the essence of participants’ experiences. Findings – QRIS is not merely a payment tool but a practical mechanism embedded in everyday business practices. It improves operational efficiency by enabling faster transactions, reducing cash handling, and simplifying service processes, while also supporting financial management through automated transaction recording and real-time cash flow monitoring. However, its impact on broader business outcomes, particularly transaction growth, remains uneven and depends on customer readiness, digital literacy, and infrastructure conditions. The study further reveals that QRIS adoption is influenced by Islamic values, particularly taysir (ease) and niyyah (intention), which imbue the use of digital payment technology with moral and religious meaning among Muslim MSMEs. Research Implication – This study extends the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) by integrating lived experience and value-based perspectives, while highlighting the importance of strengthening digital ecosystems for MSME sustainability. Originality/value – This study offers a phenomenological perspective that links operational, financial, and religious dimensions in understanding QRIS adoption among Muslim MSMEs